The Combination of Boiled Katuk and Kelor Leaves Towards Breast Milk Launch - Weni Tri Purnani; Meirna Eka Fitriasnani; Huda Rohmawati (Master of Public Health Program Institut Ilmu Kesehatan STRADA Indonesia, 2020)
The launch of breast milk on postpartum mothers should be treated appropriately to make the exclusive breast milk work smoothly. The survey result in Gampengrejo’s community health center in April 2019 was obtained 9 out of 14 postpartum mothers (64.28%) experiencing breast milk flow problems. Postpartum mothers consuming boiled katuk and kelor leaves can smooth the flow of breast milk. Many problems have been spent on the post-partum mothers on day 1 up to day 7. The purpose of this study is to determine the influence of the combination of boiled katuk and kelor leaf. The design of the research used is an experimental study with a pre-experimental design using pre-test and post-test design. The population is the mother of the postpartum on day 1 through day7 in Gampengrejo’s community health center Kediri. The sampling technique uses a simple random sampling technique and it is obtained 16 samples. The samples are given the treatment of a combination of boiled katuk and kelor leaves. The research instrument used is an observation sheet. Research results were analyzed using the Wilcoxon test. Based on the result, it shows almost all respondents breast milk that was 13 people (81.3) come out smoothly after being administered a combination of boiled katuk and kelor leaf. Based on the results of the analysis obtained ρ value 0.000 < 0.05 indicating the influence of the breast milk flow between before and after administering the combination of boiled katuk and kelor leaf. The medical staff is expected to provide information about the benefits of the combination of boiled katuk and kelor leaf for the postpartum mothers.